2014
DOI: 10.1177/1097184x14557495
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Construction of an Egalitarian Masculinity

Abstract: According to dominant cultural representations, masculinity in heterosexual relationships is signified by men's dominance, aggression, sexual promiscuity, and emotional unavailability. Yet, the preferred way of doing masculinity is context-specific, and middle-class men face increasing expectations that they engage in egalitarian relationships. In this study, I use in-depth interviews with thirty-one college-educated, heterosexual men to examine how they construct their masculinity under changing social condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…However, beyond a search for emotional authenticity, some have suggested that men's actual feelings about sexual intimacy are much more complex, and men express a feeling of anxiety around desires for sexual and emotional intimacy (Seal and Ehrhardt 2003), anxiety that still manifests in the perpetuation of gender inequality (Lamont 2015). I demonstrate below the ways that this anxiety manifests in the figure of the creep, with mixed results.…”
Section: Clare Forstiementioning
confidence: 89%
See 1 more Smart Citation
“…However, beyond a search for emotional authenticity, some have suggested that men's actual feelings about sexual intimacy are much more complex, and men express a feeling of anxiety around desires for sexual and emotional intimacy (Seal and Ehrhardt 2003), anxiety that still manifests in the perpetuation of gender inequality (Lamont 2015). I demonstrate below the ways that this anxiety manifests in the figure of the creep, with mixed results.…”
Section: Clare Forstiementioning
confidence: 89%
“…Connell 2005;Messerschmidt 2018) pervades men's popular media (K. Green and Oort 2013;Tan et al 2013;Messner and Montez de Oca 2005), and clear-cut sexual scripts privilege the development of unemotional masculine selves (Montemurro and Riehman-Murphy 2018). However, the modern, masculine self seems ambivalent on the subject of sexual intimacy and emotions (Lamont 2015;Eisen and Yamashita 2017). On the one hand, it would seem, according to some sociologists, that men may be looking for more emotional authenticity in their sexual experiences.…”
Section: Working Paper Clareforstie@farmingdaleedumentioning
confidence: 99%
“…More specifically related to reproduction, pressures to conform to hegemonic masculinity are associated with the expectation that men generally lack concern about physical and psychological health (Addis and Mahalik 2003; de Visser and Smith 2006; de Visser, Smith, and McDonnell 2009) and espouse a predatory, hypersexual heterosexuality (Pascoe 2006; Schrock and Schwalbe 2009). Thus, more egalitarian expressions of masculinity may be tied to greater involvement in and support for contraception, although this does not always entail substantial change in unequal power distribution between men and women (Lamont 2015). There is a growing literature on hybrid masculinities, which suggests that men negotiate masculinity in ways that mirror more inclusive behaviors and attitudes but leave larger hegemonic systems sustaining unequal gender relations between men and women undisturbed (Bridges and Pascoe 2014; Connell and Messerschmidt 2005; Messerschmidt 2010; Messner 2007).…”
Section: Gender and Contraceptionmentioning
confidence: 99%
“…For example, men whose partners have higher earning potential may make up for the perceived loss of masculinity by demonstrating athletic prowess. Further, young men may use egalitarian narratives when they describe their relationships with women, but often these narratives mask extant inequalities while retaining men’s gendered identities as progressive, egalitarian men (Lamont 2015). In one of the few studies about men’s supportive behaviors in reversible contraception, Fennell (2011) interviewed 30 young adults to show how men take responsibility for condoms and women for other methods, reflecting women’s continued place in the domestic sphere.…”
Section: Gender and Contraceptionmentioning
confidence: 99%
See 1 more Smart Citation